2011
DOI: 10.5194/aab-54-36-2011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sires on wide scale of milk indicators in first calving Czech Fleckvieh cows

Abstract: The possible genetic impact of sire on cattle populations, herd milk yield and milk traits (fat and protein) have been described in the literature along with its impact on some milk indicators (MIs) as somatic cell count, urea and ketones. There is a dearth of information on the impact on a series of other MIs (physical, chemical, health, technological). The goal of this study was to assess the possible effect of sire on a wide range of MIs including technological properties in Czech Fleckvieh to suggest futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 42 publications
(50 reference statements)
1
16
2
Order By: Relevance
“…The existence of signifi cant diff erences among individual breeds support the opinion that the parameter "breed" should be taken into account as one of factors that infl uence results of experiments focused on milk technological quality. An insignifi cant eff ect of breed on parameters of technological quality of milk observed in this study does not corresponds with data published by Hanuš et al (2011) who recorded them in a study with a diff erent breed of cattle.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The existence of signifi cant diff erences among individual breeds support the opinion that the parameter "breed" should be taken into account as one of factors that infl uence results of experiments focused on milk technological quality. An insignifi cant eff ect of breed on parameters of technological quality of milk observed in this study does not corresponds with data published by Hanuš et al (2011) who recorded them in a study with a diff erent breed of cattle.…”
Section: Resultscontrasting
confidence: 99%
“…For example De Marchi et al (2007) mentioned that in their experiments, milk producing by dairy cows of Holstein-Friesian breed showed the worst coagulation (including RCT) among all other breeds under study. In addition Hanuš et al (2011) observed that herd, year, and season showed a signifi cant eff ect on milk composition and its technological parameters (including RCT) of milk produced by dairy cows of the Czech Fleckvieh breed. Daviau et al (2000) mentioned that shorter RCT was associated with a decrease in the content of protein, which usually associated also with a decrease in the content of casein.…”
mentioning
confidence: 99%
“…Every part of an ejaculate processing from its collection to production AI doses is very important and affects the final quality. Sperm quality is influenced by many factors, e.g., by breed, variation between individuals, and age of the sire , Štolc et al 2009, Bezdíček et al 2010, Strapák et al 2010, Hanuš et al 2011, by feeding ration composition, content of specialised feeding supplements (Čeřovský et al 2009(Čeřovský et al , Jacyno et al 2009), environmental conditions, frequency of ejaculate collection (Wolf & Smital 2009, Karoui et al 2011, and by season of the year (Hajirezaee et al 2010) or even calendar month, especially in animal species with seasonal sexual activity (Alavi et al 2010, Król et al 2011. Collection of ejaculate and its subsequent processing present further potential risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Milk composition is affected by a number of factors, such as genetics (Hanuš et al, 2011a), nutrition (Buttchereit et al, 2011), cow's energy status (Friggens et al, 2007), season (Auldist et al, 1998;Lujerdean et al, 2009), and others (age, parity, ambient temperature).…”
mentioning
confidence: 99%